Upaya Dinas Sosial PPPA Serta PMD dalam Mengurangi Angka Perkawinan Anak di Kecamatan Kerek Kabupaten Tuban - Wudiati, Cicik; Raden Roro Nanik Setyowati (Universitas Negeri Surabaya (Unesa), 2024)
Child marriages that occur in Kerek District, Tuban Regency are in the highest ranking position based on data from applicants for marriage dispensation (Diska) in 2022 and 2023. The high rate of child marriages is caused by economic, cultural factors and the condition of out-of-wedlock pregnancies. The aim of this research is to determine the efforts made by the Social Service for Women's Empowerment and Child Protection (PPPA) and Community and Village Empowerment (PMD) in reducing the number of child marriages that occur in Kerek District, Tuban Regency and to find out what obstacles are experienced in implementing these efforts. the. The theory used in this research is structuration theory by Anthony Giddens. This research uses a qualitative method with a case study design. Data collection techniques use observation, interviews and documentation. The results of this research show that (1) the Social Services for Women's Empowerment and Child Protection (PPPA) and Community and Village Empowerment (PMD) have made efforts to reduce the number of child marriages through programs including diska counseling, women's schools, trustful family bonds and child love (Glass Shoes). ), outreach, Tuban Ronggolawe children's forum, integrated service center for women and child protection (P2TP2A), women and child protection task force (P2A) and partnerships between regional organizations (OPD). (2) In implementing this program, there are obstacles experienced by the PPPA Social Service and PMD, including (1) unreachable human resources, limited facilities and infrastructure, traditional culture, and weak law enforcement.